Acousto-optical diffraction : Broadband acousto-optic control of the rotation velocity of the radiation polarisation vector. (28th August 2018) - Kotov, V M; Kotov, E V
Abstract: A method is described for the formation of optical radiation with a rotating polarisation vector whose rotation frequency varies over a wide range. The method employs two identical acoustooptic (AO) modulators made of a gyrotropic crystal. The experimentally realised range of the rotation frequency of the polarisation vector of optical radiation with a wavelength of 0.6 × 10 -4 cm with the use of AO TeO2 cells is found to be ≈6 MHz.